Mark Manders : China. (Arnhem : ROMA, 2001)
Sequel to ‘Coloured Room with Black and White Scene’. A number of titles are now translated into three dimensional works.
This book is an ode to the world behind language, made as a substitute for a trip to China.
Engels
boek
Keywords: Manders, Mark